Plant Glutathione Transferases and Light - Gallé, Ágnes; Czékus, Zalán; Bela, Krisztina; Horváth, Edit; Ördög, Attila; Csiszár, Jolán; Poór, Péter (Frontiers in Plant Science, 2019)
The activity and expression of glutathione transferases (GSTs) depend on several less-known endogenous and well-described exogenous factors, such as the developmental stage, presence and intensity of different stressors, as well as on the absence or presence and quality of light, which to date have received less attention. In this review, we focus on discussing the role of circadian rhythm, light quality and intensity in the regulation of plant GSTs. Recent studies demonstrate that diurnal regulation can be recognized in GST activity and gene expression in several plant species. In addition, the content of one of their co-substrates, reduced glutathione (GSH), also shows diurnal changes. Darkness, low light or shade mostly reduces GST activity, while high or excess light significantly elevates both the activity and expression of GSTs and GSH levels. Besides the light-regulated induction and dark inactivation of GSTs, these enzymes can also participate in the signal transduction of visible and UV light. For example, red light may alleviate the harmful effects of pathogens and abiotic stressors by increasing GST activity and expression, as well as GSH content in leaves of different plant species. Based on this knowledge, further research on plants (crops and weeds) or organs and temporal regulation of GST activity and gene expression is necessary for understanding the complex regulation of plant GSTs under various light conditions in order to increase the yield and stress tolerance of plants in the changing environment.